Maximum Ride: Never More - Book 8 - Patterson, James 1947-; Soler, Rebecca (New York : Hachette Audio, 2012)
Max, Fang, and Dylan prepare for the ultimate confrontation as a mysterious group threatens to reduce the world's population by ninety-nine percent by killing all those who are not enhanced.
Unabridged.
Compact discs.
Read by Rebecca Soler.
Keywords: Friendship -- Fiction; Adventure and adventurers -- Fiction; Magic -- Fiction; Genetic engineering -- Fiction; Audiobooks; Children's audiobooks